Law, enviromental law and systemic thinking - Verna, Vito (2019)
Among the last years, human beings have gained awareness about the impact their activities have on the environment. Thus, the environmental rule has surfaced, departing from a connection between human actions, their consequences and the legal system.In this article, the author proposes a simile between the functioning of our mind and the environment in order to fi nd a common element: connectivity; and a method of knowledge: systemic thinking. Likewise, an analysis is made about how the systemic should influence both the environmental law and the law in general to help civilization restore the balance.